Is There Any Discrimination Towards Young Women in Indonesia’s Labor Market? - Karnadi*(1), Erwin Bramana (Universitas Prasetiya Mulya, 2019)
Gender equality is one of the most important issues in the labor market. In this paper, we want to observe the level of gender equality in Indonesia’s labor market. One of the ways to do this is to estimate the relationship between gender and salary. We obtained a sample size of 1404 white-collar Indonesian employees, which consists of several variables such as salary, gender, age, education level, university, experience, job role, managerial role, and company size. We estimated the relationship using Ordinary Least Squares and Blinder Oaxaca Decomposition, and conclude that in general, gender has no significant impact on salary after holding all other variables constant. However, when we subset the data set to only young workers, we found evidence of salary-based discrimination towards young women in Indonesia’s labor market.Keywords: gender equality, gender pay-gap, Indonesia, labor economics(1) Faculty of Economics and Business, Atma Jaya Catholic University, Jakarta, Indonesia* Corresponding Author https://doi.org/10.21632/irjbs.12.1.69-86